Consequences of the evolutionary cardiovascular challenge of human bipedalism: orthostatic intolerance syndromes, orthostatic hypertension. Issue 12 (December 2019) - Esler, Murray; Julius, Stevo; Coghlan, Benjamin; Sari, Carolina Ika; Guo, Ling; Esler, Danielle
Abstract : N/A: In quadrupeds, the arterial baroreflex has dominance in the reflex homeostatic responses, which protect against haemorrhage. In humans, it is the low pressure cardiopulmonary reflex, which protects against the analogous cardiovascular challenge of gravity-dependent venous pooling with standing. To preserve orthostatic cardiovascular homeostasis with the emergence of bipedalism in humans the low pressure reflex, a minor, subsidiary reflex in quadripeds, was co-opted. Mirroring the imperfect skeletal evolution to bipedalism, this cardiovascular development has been problematic, with dysregulation manifesting as disabling orthostatic intolerance syndromes and, paradoxically, an orthostatic hypertensive response that appears to play a role in the development of essential hypertension in some people. Improved understanding of these evolutionary faults provides new options for postural and pharmacological treatments.